2018
DOI: 10.1007/s11356-018-2264-z
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of particle size fractions on lung function of late adolescents

Abstract: Although ambient air pollution has been linked to reduced lung function in healthy students, longitudinal studies that compare the response of asthmatic and healthy adolescents are lacking. To evaluate lung function responses to short-term ambient air particulate matter (PM, PM, and PM) levels, we conducted a study on high school students aged 15-18 years. The aim of this study was to assess effects of acute exposure to ambient air particulate matter (PM) on lung function in healthy and asthmatic late adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…S2. Order of ionic components in particles followed NO 3¯> Cl¯> SO 4¯2 > Ca +2 > Na + > K + > Mg +2 > F¯> NH 4 + > NO 2¯d uring dust storm (Fig. S2a) and SO 4¯2 > NO 3¯> NH 4 + > Cl¯> Ca + 2 > Na + > K + > F¯> NO 2¯> Mg +2 during inversion (Fig.…”
Section: Results Of Ionic Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…S2. Order of ionic components in particles followed NO 3¯> Cl¯> SO 4¯2 > Ca +2 > Na + > K + > Mg +2 > F¯> NH 4 + > NO 2¯d uring dust storm (Fig. S2a) and SO 4¯2 > NO 3¯> NH 4 + > Cl¯> Ca + 2 > Na + > K + > F¯> NO 2¯> Mg +2 during inversion (Fig.…”
Section: Results Of Ionic Analysismentioning
confidence: 97%
“…Ambient air pollution is a global public health concern, especially in the metropolitan areas, that associated with cardiorespiratory diseases, reduced lung function, asthma, chronic bronchitis and increased hospital admissions [1][2][3][4]. Unfortunately, the atmospheric pollution is increasing due to the growth of population, increasing vehicles and urban expansion [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-three articles from almost all regions discussed mortality due to dust storms by means of different health problems, such as increased total non-accidental deaths, 3 , 38 , 39 , 41 , 46 , 53 - 55 , 68 - 82 cardiovascular deaths, 3 , 38 , 39 , 48 , 50 , 53 , 70 , 74 , 77 , 82 - 85 mortality due to acute coronary syndrome ( ACS), 3 , 70 , 81 , 86 and respiratory mortality. 48 , 53 , 55 , 77 , 87 Some studies reported, however, that the number of cases was not increased significantly for all-causes, 43 , 88 respiratory, 38 , 43 cardiovascular, 43 or cerebrovascular mortality.…”
Section: Short-term Health Effectsmentioning
confidence: 99%
“… 104 Also, some reported no significant association between increased dust particles and angina. 50 Bennett et al 105 reported that the dust storms were not associated with an excess of CVD hospitalizations.…”
Section: Short-term Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation